Contextos familiares y su influencia en el estado emocional durante el aprendizaje de los niños del subnivel de preparatoria de la Unidad Educativa La Inmaculada. - Tarco Guanoluisa, Mayra Janeth (2023)
The main purpose of this research is to provide information to parents so that they adopt positive attitudes that allow them to improve their family environment, its influence on the emotional state and the learning process of their children's education, thus generating a healthy coexistence among other people and thus they are achieving an integral development with the purpose of being productive people for society in the future. The general objective is: Describe the incidence of family contexts in the emotional state during the learning process of children of the high school sublevel of the La Inmaculada Educational Unit; The methodology used in the present work was the qualitative and quantitative approach, allowing to manage the statistical data for their respective analysis and interpretation.